Comparison of Clinical Trial Outcome Patterns in Patients Following Acute Coronary Syndromes and in Patients With Chronic Stable Atherosclerosis. Issue 6 (25th February 2014) - Mahaffey, Kenneth W.; Wojdyla, Daniel M.; Pieper, Karen S.; Tricoci, Pierluigi; Alexander, John H.; Lincoff, A. Michael; Brennan, Danielle M.; Bhatt, Deepak L.; Wallentin, Lars; Harrington, Robert A.
Abstract Background The transition of patients with atherosclerotic vascular disease from the acute phase of the disease to the chronic stable atherosclerosis (CSA) phase has not been well characterized. We sought to compare ischemic and bleeding outcomes in hospitalized patients enrolled in clinical trials of non–ST‐elevation acute coronary syndrome (ACS) with patients enrolled in outpatient trials of CSA. Hypothesis The risk for recurrent events will differ between the 2 populations. Methods Patient‐level outcome data were evaluated from 3 consecutive trials of patients with ACS with long‐term follow‐up and 2 trials of patients with CSA. Kaplan‐Meier curves were generated for ischemic and bleeding outcomes. Results In total, 37 370 patients were included in these analyses. Of these, 28 489 (76.2%) were from ACS trials and 8881 (23.8%) from chronic trials. During the first year of follow‐up, 1353 deaths, 1081 cardiovascular (CV) deaths, 2113 myocardial infarctions (MIs), and 397 strokes occurred across the trials. Six‐month Kaplan‐Meier event rates for CV death, MI, or stroke were higher in the ACS trials compared with the CSA trials (8.6% vs 2.7%), as were the 1‐year CV death rate (3.6% vs 1.7%) and 1‐year rates for GUSTO moderate or severe bleeding (6.0% vs 1.3%). Qualitatively, the Kaplan‐Meier curves appear to show an early increased risk as well as a continued increased risk over time. Conclusions Patients with ACS enrolled while in the hospital appear to have different risk profiles for ischemic and bleeding outcomes compared with outpatients enrolled with CSA, including those patients with ACS after the acute phase.